Rhodococcus equi pVAPN type causing pneumonia in a dog coinfected with canine morbillivirus (distemper virus) and Toxoplasma gondii - Portilho, Fábio V.R. [UNESP]; Paes, Antonio C. [UNESP]; Megid, Jane [UNESP]; Hataka, Alessandre [UNESP]; Neto, Rafael Torres; Headley, Selwyn A.; Oliveira, Thalita E.S.; Colhado, Bruna S. [UNESP]; de Paula, Carolina L. [UNESP]; Guerra, Simony T. [UNESP]; Mota, André R. [UNESP]; Listoni, Fernando J.P. [UNESP]; et al. (Elsevier, 2019)
Canine morbillivirus (previously, canine distemper virus, CDV) is a highly contagious infectious disease-causing agent that produces immunosuppressive infections and multiple clinical signs. Canine toxoplasmosis is an opportunistic disease characterized by enteric, pulmonary, and neuromuscular signs that might be confused with CDV-induced infections. Rhodococcus equi is a Gram-positive intracellular facultative bacterium that is also opportunistic in nature, and causes pyogranulomatous infections in humans and multiple host animals, although canine rhodococcosis is rare or unrecognized. The pathogenicity of R. equi is intimately related to the presence of plasmid-encoded virulence-associated proteins (Vap). Three host-adapted virulence plasmid types of R. equi have been recognized: the circular pVAPA and pVAPB are associated with equine and porcine strains, respectively, and the recently detected linear pVAPN virulence plasmid is related to bovine isolates. Nevertheless, data regarding the detection of host-adapted virulence plasmid types of R. equi isolated from companion animals are scarce. This report describes a case of an uncommon coinfection due to R. equi, T. gondii and CDV, which was diagnosed in a pet dog with respiratory distress. In this case, CDV most likely induced immunosuppression, which facilitated opportunistic infections by R. equi and T. gondii. The analysis of the virulence profile of R. equi revealed the novel pVAPN plasmid type, initially related to bovine strains. This is the second report of the bovine-associated pVAPN type in a pet dog, with an unusual coinfection with T. gondii and CDV. These findings represent a public health concern due to the close contact between pet animals and their owners, particularly because the pVAPN plasmid type was recently detected in people with HIV/AIDS from the same geographical region.
Keywords: Bovine-associated plasmid type; Canine rhodococcosis; Emerging infectious diseases; Immunocompromised patients; pVAPN